1987
DOI: 10.2172/6196790
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent solar concentrator development: Final subcontract report, 1 June 1982-31 December 1984

Abstract: Price: Microfiche A01 Printed Copy A10 Codes are used for pricing all publications. The code is determined by the number of pages in the publication. Information pertaining to the pricing codes can be found in the current issue of the following publications. which are generally available in most libraries: Energy Research Abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Numerous different fluorophores have been developed and tested for use in LSCs, including organic dyes [7][8][9], quantum dots [10][11][12][13], and rare-earth materials [14][15][16]. However, a problem common to both organic dyes and quantum dots is the effect of reabsorption resulting from an overlap of their absorption and emission spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous different fluorophores have been developed and tested for use in LSCs, including organic dyes [7][8][9], quantum dots [10][11][12][13], and rare-earth materials [14][15][16]. However, a problem common to both organic dyes and quantum dots is the effect of reabsorption resulting from an overlap of their absorption and emission spectra.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lack of photostability is typical of organic dyes is severely limiting the possibility of application in LSCs . While some ultrastable organic dyes have been lately identified and some metal–organic complexes are characterized by excellent stability, finding a dye exhibiting simultaneously the entire set of required optical property for successful application in an LSC is challenging …”
Section: Nanomaterials Application In Lscsmentioning
confidence: 99%
“…Early investigations of LSCs were pioneered by Batchelder, et al using 18 different dyes , where they found that the small Stokes shifts of the dyes leading to reabsorption on large area plates were limiting the achievable light concentration in their devices. A more comprehensive work by Friedman and Parent exhaustively investigated over 200 dyes and polymer matrices to find the most optimal dye and plastic matrix combinations. In these reports, there is a consensus that a dye with a large Stokes shift and high PLQY is a necessity to maximize the light concentration of LSCs.…”
Section: Introductionmentioning
confidence: 99%